2019
DOI: 10.18805/lr-4063
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis for yield and yield components in mungbean [Vigna radiata (L.) Wilczek]

Abstract: Combining ability analysis for yield and yield components of mungbean [Vigna radiata (L.) Wilczek] was attempted using an 8 x 8 diallel mating system both in F1 and F2 generations. Both gca and sca mean squares were significant for all the eleven characters in F1 and F2 generations, former being more pronounced for clusters per plant, pods per cluster, pods per plant, pod length, seeds per pod, 100-seed weight and seed yield per plant in F1 and for all the characters except days to maturity, seeds per pod and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…These findings provide proof of the closeness of a highly significant amount of genetic variability among the mungbean parents and their respective hybrids (F 1 ), which may encourage genetic improvement utilizing such genetic pools of mungbeans. These outcomes were in agreement with those reported by Latha et al [11], Kumar et al [42], Sopan et al [13], and Viraj et al [34]. The mean square of general combining ability (GCA) and specific combining ability (SCA) were significant for all the characters.…”
Section: Analysis Of Variance (Anova) For Combining Abilitysupporting
confidence: 92%
See 3 more Smart Citations
“…These findings provide proof of the closeness of a highly significant amount of genetic variability among the mungbean parents and their respective hybrids (F 1 ), which may encourage genetic improvement utilizing such genetic pools of mungbeans. These outcomes were in agreement with those reported by Latha et al [11], Kumar et al [42], Sopan et al [13], and Viraj et al [34]. The mean square of general combining ability (GCA) and specific combining ability (SCA) were significant for all the characters.…”
Section: Analysis Of Variance (Anova) For Combining Abilitysupporting
confidence: 92%
“…Several professionals have used the combining ability to analyze the genetic impact and genetic value of parents in various crops. The findings were well matched with earlier publications [11][12][13]34]. Combining ability and heterosis has been successfully used to reproduce mungbeans [11][12][13].…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…and Viraj et al (2020). On contrary,Latha et al (2018) reported comparatively higher additive variance for branches per plant andNath et al (2018) for days to 50% flowering, primary branches, clusters per plant and seed yield/plant in greengram.…”
mentioning
confidence: 91%